2011
DOI: 10.1128/mcb.05583-11
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RhoGAP22 as an Akt-Dependent Regulator of Cell Motility in Response to Insulin

Abstract: Insulin exerts many of its metabolic actions via the canonical phosphatidylinositide 3 kinase (PI3K)/Akt pathway, leading to phosphorylation and 14-3-3 binding of key metabolic targets. We previously identified a GTPase-activating protein (GAP) for Rac1 called RhoGAP22 as an insulin-responsive 14-3-3 binding protein.Insulin increased 14-3-3 binding to RhoGAP22 fourfold, and this effect was PI3K dependent. We identified two insulin-responsive 14-3-3 binding sites (pSer 16 and pSer 395 ) within RhoGAP22, and mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…By using this antibody, we have analyzed endogenous ARHGAP22 expression in various cell types. Among cell lines tested, we found that mouse C2C12 myoblasts express endogenous ARHGAP22 protein [14]. We therefore determined localization of endogenous ARHGAP22 in C2C12 cells.…”
Section: Resultsmentioning
confidence: 99%
“…By using this antibody, we have analyzed endogenous ARHGAP22 expression in various cell types. Among cell lines tested, we found that mouse C2C12 myoblasts express endogenous ARHGAP22 protein [14]. We therefore determined localization of endogenous ARHGAP22 in C2C12 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Hence future experiments must dissect and account for all the GAPs in a given cell to define the total contribution they make to the differential regulation of GTPase activity. ARHGAP25 and ARHGAP22 genes are expressed in all tissues, but spleen and peripheral leucocytes have the highest level of ARHGAP25 products [61], whereas vascular endothelial cells have the highest levels of the ARHGAP22 gene products [55,68,69]. Podocytes are particularly enriched in FilGAP, up-regulating its expression ∼70-fold when they differentiate in situ [24,60].…”
Section: Localization and Tissue Distribution Of Arhgapsmentioning
confidence: 99%
“…Mutation of Ser 402 to alanine reduced FilGAP activity in cells, but only modestly compared with the substitution of all six sites [24,26]. If this hypothesis is true, phosphorylation of FilGAP could regulate turnover of Rac through associations with other cellular components and/or by facilitating dissociation from FLNa under force [69,72] (see below). More likely is that phosphorylation of FilGAP leads to differential targeting of the RacGAP, either altering membrane binding or by exposing a new partner interaction.…”
Section: Regulation Of Gap Activity By Phosphorylationmentioning
confidence: 99%
See 2 more Smart Citations